The method for staining of anterior lens capsule in cases with small and rigid pupils - V. Kumar; M. A. Frolov; I. Ye. Makovetskaya; E. V. Bozhok (Oftalʹmologiâ)
Purpose: to evaluate the safety and effectiveness of proposed method for staining with trypan blue anterior lens capsule in cases with small and rigid pupils.Methods: the safety and effectiveness of the proposed method was evaluated in 169 cases having small and rigid pupils of III and IV grade. Surgical steps included: irrigation of anterior chamber with small amount of air, enough to block the pupil; irrigation of posterior chamber with little amount of dye followed by aspiration of air bubble. the excess dye came out and stained the capsule in pupillary area.Results: No difficulty was encountered in irrigating the posterior chamber with dye. Uneven staining of the capsule was noticed in 16 cases (9.5%). In 3 cases (1.8%) extensive staining of iris and posterior capsule was observed. Continuous curvilinear capsulorhexis was performed successfully in 97.6% cases. In 4 cases there was radial run of the rhexis extending up to posterior capsule. Postopera- tive inflammation of 1st and 2nd degree was observed in 5.9 and 23.1% cases, which was related to unavoidable trauma to iris tissue during pupil stretching.Conclusion: the proposed method of capsule staining in cases with small and rigid pupils is safe and effective.